MANAGING SCULPTURE WORKSHOPS THROUGH DIGITAL TWINS - Nayak, Dinesh Kumar; Devi S; Poornima P; Munjal, Sonia; Verma, Subhash Kumar; Doifode, Vaibhaw R (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The use of Digital Twin (DT) technology in art and craft has the potential to entirely transform the way that often complicated creative processes are managed, as in modelling classes. DTs can facilitate the constant exchange of data between the real and digital worlds by digitally replicating the real-time conditions of workshops using sensors and 3D modeling software incorporated into an IoT-based platform. This mixed-methods study includes interviews, site observations of sculpture practice, and computer modeling to inherently develop a framework for working with DTs in sculpture practice. The proposed approach allows monitoring tools, materials, and artist’s work in real time and the prediction analytics help with maintenance planning and efficient use of work flow. What we learnt from case study groups is that the use of DTs not only increases speed of production but keeps the artistic purpose, correctly recording the creative decisions digitally. It also grants the learner the ability to share what they know through the interaction with virtual representations of the shaping process. The study concludes that Digital Twins can be used for conducting workshops in the future that are sustainable as well as compatible with the Industry 4.0 technologies. In the management of cultural items, this system makes it possible to digitize the creative industries and protect cultural heritages by making the whole process data-driven.